INTEGRATING TASK-BASED LANGUAGE TEACHING TO IMPROVE COMMUNICATION SKILLS AMONG FIRST-YEAR ENGINEERING STUDENTS: A CASE STUDY AT GOVERNMENT ENGINEERING COLLEGE, MODASA - Bhayani, Deven; Chauhan, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of Task-Based Language Teaching (TBLT) in language teaching for engineering students has gained distinction due to its focus on practical, meaningful language use. This study investigates the effectiveness of TBLT in improving the communication skills of first-year engineering students at Government Engineering College, Modasa. Specifically, the research addresses the linguistic challenges faced by students from vernacular backgrounds and aims to enhance their grammar, technical vocabulary, and writing fluency through a series of task-based activities designed to technical education. The results from pre- and post-tests indicate a significant improvement in the experimental group compared to the control group, highlighting the potential of TBLT to bridge communication proficiency gaps in technical education. These findings contribute to the broader discourse on effective syllabus design for engineering education and second language acquisition (SLA), while considering the linguistic dynamics specific to Gujarat.